Metodologías activas en el desarrollo del pensamiento crítico en los estudiantes del sexto año de Educación General Básica de la Escuela General Vicente Anda Aguirre, de la parroquia Las Naves, cantón Las Naves, provincia Bolívar, periodo 2010 - 2011 - Calderón Quisirumbay, María Magdalena (2012)
Active methodologies in the development of the critical thought in the students of the sixth basic year of general education of the general school Vicente Walks Aguirre, of the Parish the Ships, Corner the Ships, Province Bolivar, period 2010 - 2011, subject of investigation that is justified by the necessity to elaborate an educative product of diffusion that treats on the active methodologies for the development of the critical thought, with the purpose of fortifying the learning significant and to contribute to the integral formation of the student contributing with it to the good one for living. Also he arises like an answer to the formation exigencies of the new millennium, that demands the formation of students with abilities and competitions developed for the analysis and valuation of the information, the solution of real problems, intention that is obtained on the basis of an agreed methodological process and that impels this one intention. From the Pedagogical Vanguards as well as the proposal of curricular update of the Ecuadorian basic education they base the formation processes on the postulates of pedagogic critical, that locates to the students one like main protagonist of the learning, within different methodological structures, with predominance of the cognitivistas and constructivist’s routes. The educational one in these circumstances is the person in charge of the scholastic atmosphere, of the mediation of the methods, processes, activities, for the treatment of the contents and experiences of learning that it generates after the integral formation of his students. In her development of thought critical imposes since a process by means of which is considered it is used the knowledge and the intelligence, therefore intellectually is disciplined of active and capably to conceptualize, to apply, to analyze, to synthesize and/or to evaluate information compiled or generated by observation, experience, reflection, reasoning or communication as a guide towards the belief and the action, homing, is autodisciplinado, autoregulado and autocorregido that being put under rigorous standards of excellence and conscious dominion requires, this implies an effective communication and to have abilities of solution of problems. Different investigations as well as evaluations from the student performance throw discouraging results, reason for which this investigation was made, through surveys to educational, students and parents of family of the sixth basic year of education of the school Vicente Anda Aguirre, interviews to experts on the subject, observation of educational and student driving, and the bibliographical compilation, to establish the incidence who have the active methodologies in the development of the critical thought in the students. Tabs and analyzed the data the hypothesis of study through chi is verified square, concluding that the active methodologies influence positively in the development of the critical thought, favored by the mediation adapted with the treatment of the contents and the use of the intellectual standards. Consequently one sets out intentionally to work actively with the students generating actions directed and planned for the development of the critical thought of the students, favoring a cooperative learning generating cosy, stimulating pedagogical an atmosphere that motivates and causes the intellectual use of the operations and abilities necessary to make of the students critical thinkers. In chapter I it includes the theoretical frame, constituted by the scientific theory, with fundamental aspects of the active methodologies, the active methods, the active learning, significant learning, theory of the significant learning, the constructivism according to Jean Piaget, Vigotsky and its contribution to the constructivist theory, the pedagogical models and general didactic principles. The development of the critical thought, with the conceptualization of the thought, evolution, elements, critical characteristic, educational thought that stimulates the critical thought in the students, the resolution of problems. Strategies that foment or promote the critical thought, critical and critical thought, didactic reading of the critical thought, reasoning logical, approach theoretical and technical to develop the critical thought, critical theory. The legal frame, with the dispositions constitutional and normative that sustain the investigation. The conceptual theory and referential theory that it includes historical review of the school, geographic location of the corner the Ships, population, temperature, climate, vegetation, religion, means of production and sustenance, celebrations, and historical review of the corner the Ships. Chapter II it establishes the methodological strategies, the type of investigation by the intention, the level, the place, the techniques and instruments for the data collection, the temporary dimension, the universe and shows, the data processing, the methods. Chapter III The analysis and interpretation of results, distributed in results of the survey directed to the students, educational and parents of family, the verification of hypothesis, the conclusions and recommendations. Chapter IV it contains the proposal with its title, introduction, the objectives: general and specific, the development, the evidences of the application and the results of the application.